A Proposed Criteria for Evaluting Cloud based Systems - Bello, Sururah Apinke (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
A number of Cloud Providers have sprung up with different offers ranging from providing instances that looks much like physical hardware to application domain-specific offers. This study intends to propose a set of review criteria to evaluate existing Cloud computing providers to high level information about this emerging way of IT provisioning. Existing Cloud providers in the Iaas, Paas and SaaS were considered using, Architecture, Application Programming Interface, User Interface, Security, Fault tolerance and Scalability, Software implementation, Monitoring, Payment and Performance. This study is to assist Cloud users and researchers in making important decision in using Cloud Systems. The study exposed a refined method of further classification of Cloud based System. The classification will enable users to know open systems that are readily available for research, commercial systems for big projects and also be a good starting point for new comers into Cloud Computing environment.